'If I was King of India I would Get All the Horns Out of Cars': A Qualitative Study of Sound in Delhi. (14th August 2017) - Patsarika, Maria; Schneider, Tatjana; Edwards, Michael
Abstract: In this article we present an experimental sonic space—the mobile noise abatement pod (mNAP)—constructed and used over a two‐week period in Delhi, India, during December 2014. The interdisciplinary project, involving a composer, designer, carpenter, development scholar, filmmaker, graphic designer and sociologist, sought to investigate how noise, including honking (one of the most prevalent sounds in Indian cities), is perceived. The fieldwork reveals noise to be a complex contextual, spatial and personal experience that is as much about habit as it is about identity and class, intimately related to economic inequality and inherently connected to social justice. The article suggests that attempts to reduce levels of noise need to take into account its meaning and position—by whom and how narratives of noise reduction are constructed and reproduced.